PENGUKURAN KUALITAS PELAYANAN KARTU PRA BAYAR CDMA BERDASARKAN KEPUASAN PELANGGAN - Rakhma Oktavina; Ivan Setia Laksana (Universitas Gunadarma, 2012)
Telecommunication development was accompanied by technological advances in the field of cellular. But until now most particularly CDMA operator service users still complain about some services are generally considered unsatisfactory. The purpose of this study was to determine the level of customer satisfaction for prepaid card services in CDMA, by identifying customer expectations and perceptions. Case studies carried out on customer service user CDMA prepaid card in Depok Municipality using the method of service quality (reliability and assurance). Data processing to produce the attributes that need to get the repairs, which consists of signal quality is less good, easy conversation is interrupted, the grievance can not be addressed properly by the customer service, it is difficult to deliver a complaint to customer care and customer service do not understand about customers need.Keywords: Service quality, customer satisfaction, servqual.AbstrakPerkembangan telekomunikasi dewasa ini ternyata diiringi dengan kemajuan teknologi dalam bidang seluler. Namun hingga kini sebagian besar pengguna layanan operator terutama CDMA umumnya masih mengeluhkan beberapa pelayanan yang dinilai belum memuaskan. Tujuan penelitian ini adalah mengetahui tingkat kepuasan pelanggan terhadap pelayanan jasa kartu pra bayar CDMA, dengan mengidentifikasi harapan dan persepsi pelanggan. Studi kasus dilakukan terhadap pelanggan pengguna jasa kartu pra bayar CDMA di Kotamadya Depok menggunakan metode service quality (servqual). Pengolahan data menghasilkan atribut yang perlu mendapatkan perbaikan, yaitu terdiri dari kualitas sinyal kurang bagus, percakapan mudah terputus, penyampaian keluhan tidak dapat ditanggapi dengan baik oleh customer service, sulit dalam menyampaikan keluhan kepada customer care dan customer service tidak dianggap memahami kebutuhan pelanggan.Kata Kunci: Kualitas pelayanan, kepuasan pelanggan, servqual.